2010
DOI: 10.1212/wnl.0b013e3181df091b
|View full text |Cite
|
Sign up to set email alerts
|

Generic antiepileptic drugs and associated medical resource utilization in the United States

Abstract: Generic antiepileptic drug use was associated with significantly greater medical utilization and risk of epilepsy-related medical events, compared to brand use. This relationship was observed even in patients characterized as stable. AED = antiepileptic drug; CI = confidence interval; ER = emergency room; HR = hazard ratio; ICD = International Classification of Diseases; IRR = incidence rate ratio.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 25 publications
(11 reference statements)
1
59
0
8
Order By: Relevance
“…The substitution of Lamictal® for a generic drug in epileptic patients, evaluated by 71 pharmacists and 130 physicians, showed an increase in seizures (Makus, McCormick, 2007). Another study observed that the interchangeability did not reduce cost, because it generally results in an increase and/or addition of another drug to treatment and also increases medical utilization (Labiner et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…The substitution of Lamictal® for a generic drug in epileptic patients, evaluated by 71 pharmacists and 130 physicians, showed an increase in seizures (Makus, McCormick, 2007). Another study observed that the interchangeability did not reduce cost, because it generally results in an increase and/or addition of another drug to treatment and also increases medical utilization (Labiner et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, Aptiom can be administered with or without food, and tablets can be administered whole or crushed. [2][3][4] Another key aspect is the frequency of dosing, since most patients prefer medications that are taken less frequently. Tegretol-XR and Trileptal are twice-daily formulations, and the rest of the medications are once daily.…”
Section: Administration Titration Dosingmentioning
confidence: 99%
“…However, because small differences in pharmacokinetics can result in significant side effects or breakthrough seizures, automatic substitutions without notification of the neurologist should not be done routinely. [1,2] …”
Section: Introductionmentioning
confidence: 99%
“…have concluded that there really does not seem to be any conclusive association between generic substitution and either loss of seizure control or new, treatment-emergent adverse effects (2), although there clearly is a suggestion that when generic substitution occurs, expenditures of resources goes up (3,4).…”
Section: Generic Antiepileptic Drugs: How Good Is Close Enough?mentioning
confidence: 99%